Togo- Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Togo's risk of external debt distress continues to be moderate, while the overall risk of debt distress is high—unchanged from the previous Debt Sustainability Analysis (DSA) published in December 2018. While the mechanical results point to a low risk of external debt distress, judgment was applied given vulnerabilities arising from high domestic debt, which could, for example, likely lead to a reprofiling operation that would lead to an increase in external debt. Togo's public debt is on a downward trajectory despite an increase in 2018 compared with 2017. Togo's high public debt is the result of, among other factors, high deficits, contingent liabilities, and accumulated arrears. There is very little space to absorb shocks on total public debt. Baseline projections show that Togo's PV of total PPG debt (external plus domestic)-to-GDP ratio will decline below the new debt distress benchmark of 55 percent starting in 2023, down from 72 percent in 2018—with the bulk constituting domestic debt obligations. This analysis highlights the need for sustained fiscal consolidation, improved debt management, and strong macroeconomic policies to reduce the public debt to prudent levels over the medium term.